Resiliência e autocuidado de pessoas idosas com diabetes mellitus - Mateus Carneiro Vicente; Cleane Rosa Ribeiro da Silva; Cláudia Jeane Lopes Pimenta; Maria Cristina Lins Oliveira Frazão; Tatiana Ferreira da Costa; Kátia Neyla de Freitas Macedo Costa (Rev Rene, 2019)
Objective to associate resilience levels and self-care activities in elderly people with diabetes mellitus.Methods a cross-sectional study was carried out with 96 elderly patients hospitalized for complications of diabetes mellitus in medical and surgical clinics of a university hospital. Data were collected through interviews, Resilience Scale, and Diabetes Self-Care Activities Questionnaire, being analyzed by descriptive and inferential statistics.Results elderly patients with low resilience demonstrated statistically significant higher averages of week days dedicated to self-care activities such as in the axes medication, foot care, and blood glucose monitoring.Conclusion a statistical association between resilience and self-care was identified in the areas of Medication, Foot Care and Blood glucose monitoring, with evidence of higher averages among elderly patients who showed low resilience, which shows a lower adherence of these individuals to non-pharmacological activities.